Chemical risks associated with consumption of shellfish harvested on the north shore of the St. Lawrence River's lower estuary. - Gagnon, Fabien (2004)
Shellfish have the capacity to accumulate chemical contaminants found in their biotope and therefore present a potential risk for consumers. This study was conducted to assess the chemical risks associated with consumption of shellfish harvested on the north shore of the St. Lawrence River's lower estuary. A survey was carried out on 162 recreational harvesters, and shellfish were sampled for chemical contaminant analysis. We quantified 10 metals, 22 polycyclic aromatic hydrocarbons (PAHs), 14 polychlorinated biphenyls (PCBs), and 10 chlorinated pesticides. We subsequently evaluated cancer and noncancer risks for four consumption scenarios based on our survey results and published results. Soft-shell clams (Mya arenaria) were by far the most consumed shellfish species. Of the 56 selected contaminants, 36 were detected in the 23 homogenates of soft-shell clam meat. None of the contaminants found in the soft-shell clams were associated with intakes that exceed the main exposure limit recommendations proposed to prevent noncancer effects. However, several limits must be considered before drawing conclusions about the relative safety of shellfish consumption regarding this end point. Furthermore, inorganic arsenic and PCBs were present in sufficient concentrations to lead to cancer risks exceeding the level often considered acceptable for environmental exposure (1 x 10 (-4) to 1 x 10(-6)) in each of the four scenarios, even for the lowest observed scenario of 15 meals of soft-shell clams per year.